Towards a common migration policy: potential impact on the EU economy - Gudrun Biffl (Zeitschrift für ArbeitsmarktForschung - Journal for Labour Market Research, 2006)
There is no simple answer to the question of the potential impact of migration on the EU economy. EU migration policy is expected to meet the requirements of economic and social policy, in particular of the Lisbon Agenda, as well as national cultural, political, strategic and security imperatives. The problem is complicated by different national traditions in social organisation, which are deeply rooted in history and which have resulted in different migration models within the EU. Moreover, what is an issue in its own right is immigration as a tool to counter the negative impact of population ageing on economic growth and the pressure on public funds. Another aspect of migration concerns the internationalisation of production and its contribution to the diversification of the productive structure of the EU and its member states. Further, migration may also contribute to the growth of the informal economy, an aspect of concern in member states with large shares of the informal sector in GDP. Yet another question to be resolved is the role of migration in the flow of trade in goods and services within an enlarged Europe and between the EU (25) and the rest of the world. The distinction between migration and trade in services (mode 4) is important for judging the impact on the labour market, as the regulatory mechanisms differ. The paper addresses all the above issues. As with employment, education and social policies, a common understanding about the impact of various possible routes of migration policies on the societies of the member states has to be obtained before entering a process of policy coordination towards eventual convergence. The paper focuses on ways in which different policies on various categories of migration - labour migration, family reunification, refugee and asylum-seeker intake - and the free movement of service providers can differentially impact the EU economy, calling for a complex mix of policy interventions to address the various socio-economic challenges emanating from them.
Keywords: 330; Wanderungspolitik; Einwanderungspolitik; europäische Integration; Wirtschaftsentwicklung; Wirtschaftspolitik; Sozialpolitik; demografischer Wandel; Altersstruktur; Bevölkerungsstruktur; Produktion - Internationalisierung; EU-Binnenmarkt; Gütermarkt; Liberalisierung; Außenhandel; Dienstleistungen; Schattenwirtschaft; Arbeitsmigration; Familiennachzug; Asylpolitik; Flüchtlinge; EU-Osterweiterung; Arbeitsmarkt; Integrationspolitik; Europäische Union